PENANGGUHAN KES DI MAHKAMAH SYARIAH: CABARAN DAN PENYELESAIAN - Abdullah, Raihanah (Jurnal Syariah, 2009)
The media plays an important role in circulating appropriate information to the public. In the mid-1990s, the media associated many issues pertaining Islamic Legislation to the Syariah Court in Malaysia. The said matter arose due to dissatisfaction of the public especially women; who are frustrated with the justice administration of the Syariah Court. Among the issues brought up were delays by the Syariah Court in resolving cases. This situation has caused oppressive in women. The way media described the issue gave negative impression to the image of the Syariah Court as the Islamic Institution of Justice in Malaysia. This has caused many parties to peruse in obtaining further details of the situation. As a result, various positive steps are taken by the authorities to upgrade the administration quality in the Syariah Court. This refers specifically on the settling adjourned cases in the Syariah Court. Based on current studies, there are lesser comments made upon the Syariah Court as reported by the local medium especially on the issue of cases adjournment. Hence, this paper aims to argue the fact that despite the heavy criticism and bad images crafted towards the Syariah Courts, the media, NGOs and the women themselves undoubtedly became the pressure group that contributed to the upgrade of the justice administration in the Malaysian Syariah Court.